Jejunitis and brown bowel syndrome with multifocal carcinogenesis of the small bowel - Raithel, Martin; Rau, Tilman; Hagel, Alexander; Albrecht, Heinz; De Rossi, Thomas; Kirchner, Thomas; Hahn, Eckhart Georg (World Journal of Gastroenterology, 2015)
This is the first report describing a case where prolonged, severe malabsorption from brown bowel syndrome progressed to multifocally spread small bowel adenocarcinoma. This case involves a female patient who was initially diagnosed with chronic jejunitis associated with primary diffuse lymphangiectasia at the age of 26 years. The course of the disease was clinically, endoscopically, and histologically followed for 21 years until her death at the age 47 due to multifocal, metastasizing adenocarcinoma of the small bowel. Multiple lipofuscin deposits (so-called brown bowel syndrome) and severe jejunitis were observed microscopically, and sections of the small bowel showed dense lymphoplasmacytic infiltration of the lamina propria as well as blocked lymphatic vessels. After several decades, multifocal nests of adenocarcinoma cells and extensive, flat, neoplastic mucosal proliferations were found only in the small bowel, along with a loss of the mismatch repair protein MLH1 as a long-term consequence of chronic jejunitis with malabsorption. No evidence was found for hereditary nonpolyposis colon carcinoma syndrome. This article demonstrates for the first time multifocal carcinogenesis in the small bowel in a malabsorption syndrome in an enteritis-dysplasia-carcinoma sequence.
EVALuna2:1973